CGIAR/IFPRI innovation: Linking of biophysical and economic models to capture the impact of climate change and derive projections of major food security indicators to 2050 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The PDGE was developed and applied to analyze the impact of climate change on Philippine agriculture. The results of the analyses where use to make some important policy recommendations.